Determinan Sosial Ekonomi Terhadap Pendidikan Anak Disabilitas di Indonesia - Isra Yeni; Dary Fawwaz Mahmud (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the socioeconomic determinants of the education of children with disabilities in Indonesia. The factors examined include per capita household expenditure, education of the head of household, occupation of the head of household, household size, child's gender, and area of residence. The methodology used was descriptive and associative quantitative research with secondary data from the 2020 National Socioeconomic Survey (SUSENAS). Data analysis was conducted using a logistic regression model. The results show that per capita household expenditure, education of the head of household, and area of residence have a positive and significant influence on the education of children with disabilities. Household size has a negative and significant influence. Meanwhile, child's gender and occupation of the head of household have a positive but not statistically significant influence.